Caffeine improved time to exhaustion but did not change alternative maximal accumulated oxygen deficit estimated during a single supramaximal running bout - De Araujo Bonetti De Poli, Rodrigo [UNESP]; Miyagi, Willian Eiji [UNESP]; Nakamura, Fabio Yuzo; Zagatto, Alessandro Moura [UNESP] (Human Kinetics, 2016)
The aim of the current study was to investigate the effects of acute caffeine supplementation on anaerobic capacity determined by the alternative maximal accumulated oxygen deficit (MAODALT) in running effort. Eighteen recreational male runners [29 ± 7years; total body mass 72.1 ± 5.8 kg; height 176.0 ± 5.4cm; maximal oxygen uptake (VO2max) 55.8 ± 4.2 ml·kg-1 ·min-1] underwent a graded exercise test. Caffeine (6 mg·kg-1) or a placebo were administered 1 hr before the supramaximal effort at 115% of the intensity associated with VO2max in a double-blind, randomized cross-over study, for MAODALT assessment. The time to exhaustion under caffeine condition (130.2 ± 24.5s) was 11.3% higher (p = .01) than placebo condition (118.8 ± 24.9 s) and the qualitative inference for substantial changes showed a very likely positive effect (93%). The net participation of the oxidative phosphorylation pathway was significantly higher in the caffeine condition (p = .02) and showed a likely positive effect (90%) of 15.3% with caffeine supplementation. The time constant of abrupt decay of excess postexercise oxygen consumption (τ1) was significantly different between caffeine and placebo conditions (p = .03) and showed a likely negative effect (90%), decreasing -8.0% with caffeine supplementation. The oxygen equivalents estimated from the glycolytic and phosphagen metabolic pathways showed a possibly positive effect (68%) and possibly negative effect (78%) in the qualitative inference with caffeine ingestion, respectively. However, the MAODALT did not differ under the caffeine or placebo conditions (p = .68). Therefore, we can conclude that acute caffeine ingestion does not modify the MAODALT, reinforcing the robustness of this method. However, caffeine ingestion can alter the glycolytic and phosphagen metabolic pathway contributions to MAODALT.
Keywords: Anaerobic capacity; Energetics; Ergogenic